(untitled) (GYMNASIUM, 2020)
Academic performance and adapting children to the needs of social life, both within and outside the school, is a priority for both parents and teachers. The constantly changing ideals of today’s society make the intelligence acquired from the study of disciplines in the school curriculum insufficient for most students. There are well-known cases where most of the general pupils whose results during school years clearly exceeded the success of their colleagues, but who fail to realize their intellectual potential in terms of their work, without practical skills and social skills. There is also the reverse of this situation, namely students who, although poorly equipped intellectually, demonstrate a good social adaptation to a wide variety of contexts and are regarded as successful people. In their desire to overcome this apparent paradox, researchers have introduced a number of new terms, including emotional intelligence.